Unpacking the Black Box of Lexical Inferencing: Briefing the Factors Affecting L2 Learners’ Lexical Inferencing - Mohebbi, Zahra; Mohebbi, Hassan (Advances in Social Sciences Research Journal, 2014)
Lexical inferencing (LIF) is one of the major strategies which second language (L2) learners resort to in performing reading tasks and L2 vocabulary learning. However, the majority of L2 learners are not able to make accurate LIF due to different factors which have effect on an L2 learner’s ability of successful LIF. The present paper aims at unpacking the black box of LIF. Therefore, this study briefs the factors which play key roles in LIF, in particular reader- and text-based factors. Reader-based factors include L2 proficiency, L2 vocabulary knowledge, paying attention to details, cognitive and mental effort of L2 learners, L2 grammar knowledge, and background knowledge. Moreover, text-based factors are Word characteristics, text characteristics, the presence of contextual clues, and topic familiarity. Additionally, the implications and suggestions for future L2 research are discussed in detail.